Propuesta de concienciación ciudadana para el manejo integral de desechos sólidos del centro urbano de la parroquia Capiro - Ordóñez Galarza, Gabriela Lisbeth (2016)
The present research work is part of the reason why the residents of the Capiro Parish Urban Center do not carry out an adequate classification of solid waste, the main objective is to promote environmental education so that the inhabitants contribute Significantly reduce environmental pollution. The objectives set out were fully complied with during the course of the research, which contributed valuable information to the population on the proper treatment of both organic and inorganic waste, as well as the various ways in which waste can be reused Thus achieving an environmental education in the inhabitants of the urban center of Capiro Parish. The main findings were determined in the research process, establishing how the causes of inadequate solid waste management affect environmental contamination, which are presented through variables that affect quality of life. In the findings found the lack of environmental education in the inhabitants of the urban center of Capiro Parish, is the reason why they do not classify the garbage generating a serious problem in the community. During the investigation, the methodology of the scientific method was used with its auxiliary methods, techniques and instruments, which revealed the problem under study that allowed the collection of information that identifies the problem in the Capiro Parish and its effects on the quality of Life of the residents.